Leadership Derailment: Does Self-Leadership Matters? - Sejeli, Dayana Syuhana; Mansor, Nurnaha Abu (International Journal of Economics and Financial Issues, 2015)
Business conditions today are different from what they were in the past. Public sectors are becoming more dynamic, intricate, and ambiguous. Consequently, these amplify the possibility of leadership derailment among leaders in the public sectors. Although, leadership is a popular research topic, study on leadership derailment is however still relatively new. Hence, knowledge on this construct is quite limited. Furthermore, little is commonly understood on factors that encourage and facilitate leadership behaviors particularly in complex and dynamic work environments as previous studies on derailment involved organizations that are relatively stable in nature. Thus, to gain a better understanding on this construct especially within the context of today public sectors’ environments, it is imperative to revisit the current derailment theme. Akin to the early study on leadership derailment (that compares traits of successful and derails leaders), this review seeks to understand the construct by evaluating both leadership competencies and derailment factors. Finding indicates there is indeed a missing element in the existing derailment theme, which the author believes as an important factor in leadership derailment. With support from Systemic Leadership Theory, the author further justified the significance of the new element. Keywords: Leadership Derailment; Self-Leadership; Leadership Competencies JEL Classifications: M00